Material Research for the Production of Outdoor and Kitchen Knife Blades at Low Costs - Bruçi Mirlind; Bajrami Xhevahir; Bruçi Ari; Bruqi Qendrim (Journal of Mechanical Engineering, 2023)
In today’s modern times, consumers have changed the idea of shopping. They want a functional product with performance at a low price. On the other hand, the consumer demands a variety of products in the market in terms of dimensions and usability. As the requirements are different, the engineers are challenged with different tasks related to the design of production systems, process design, organization and marketing. In this research, we will present some of the special materials used for knife blades manufactured worldwide. The proper selection of materials and their thickness significantly affects the production price, processing method, corrosion resistance, mass. Special emphasis in the work is devoted to the design of the knife blade for household requirements, model ARIA22, made of EN 1.4028 stainless steel material. It describes the work of the die block, blanking punch, the necessary energy parameters for the realization of the processing process with piercing and punching, as well as the profitability of the production.